A defeasible reasoning web service - Rotstein, Nicolás D. (2006)
In this article we outline a research line whose main goal is to give access to the software agents inhabiting the Web to a powerful inference service built around Defeasible Logic Programming (DeLP), a formalism that combines features of Logic Programming with Defeasible Argumentation. To do so, the web service prototype we proposed is the next logical step to take in order to allow agents to draw conclusions through DeLP within the Semantic Web.